Direct and Indirect Effects of Self-Efficacy and Metacognitive Skills on Biology Learning Outcomes: The Mediating Role of Self-Regulated Learning - Asryani Intan Palullu'; Arsad Bahri; Muhiddin Pallennari; Andi Citra Pratiwi (Universitas Syiah Kuala, 2026)
This ex post facto study was conducted in response to the need to understand factors influencing students’ cognitive learning outcomes in biology. It aimed to examine the effects of self-efficacy, metacognitive skills, and self-regulated learning on students’ cognitive learning outcomes. The population comprised all grade XI students at a public high school in Makassar, Indonesia, with a sample of 269 students selected through cluster sampling. Data were collected using questionnaires on self-efficacy, metacognitive skills, and self-regulated learning, as well as a biology learning outcomes test. The data were analyzed using path analysis with the assistance of SPSS. The results indicate that self-efficacy and metacognitive skills have both direct and indirect effects on cognitive learning outcomes through self-regulated learning. Self-regulated learning also functions as a mediating variable in these relationships. In conclusion, self-efficacy and metacognitive skills have a significant influence on biology learning outcomes, both directly and through the mediation of self-regulated learning, emphasizing the critical role of internal learning regulation in enhancing academic achievement